THE ARGENTINEAN DICTATORSHIP FACES THE OUTBREAK OF THE SALVADORAN CIVIL WAR (1977-1982): CONTINENTAL PROJECTION AND “SHARED EXPERIENCES” - Molinari, Lucrecia (2018)
The present text aims to describe the diplomatic relations between the Argentine government and the Salvadoran, between 1977 and 1982. The article is based on the communications that the Argentine Embassy in El Salvador sent to the Argentine Foreign Ministry. The article emphasizes the official performance of the Argentine dictatorial government. This is due to the type of documents used – all of them are official, both secret and public. For that reason, the article does not address the issue of extraterritorial and clandestine activities that were carried out in the period. These activities constitute an object of study of recent approach. The present article sought to propose a medium-term periodization. This periodization is divided into seven stages of diverse duration and is marked by important events in the relationship between both governments. It is oriented to describe the Argentine geopolitical strategy. This strategy consisted in becoming a “qualified substitute” of the United States as regards the leadership of the struggle against subversion in the continent.